Análise de pontos de captação de água superficial para supressão de incêndios florestais em Nova Ubiratã/MT - Lemes, Andyara Ferreira (2021)
Wildfires are considered to be one of the biggest threats for Amazon forests, and it is important to understand how and where they occur most frequently and what are the main methods of suppression. Knowing the location of points for capturing water helps in the suppression of forest fires, having a direct impact on the transport time interval and the cost of the operation. This study provides a comprehensive assessment of the temporal dynamics of hotspots and the impact of Land Use Land Cover change (LULC), associated with the conditions of transport infrastructure and the flow of water courses, to determine points of capture of surface water for the suppression of forest fires in the municipality of Nova Ubiratã/MT. The agricultural expansion of the municipality grew 492% from 1998 to 2020. We found a strong correlation between the annual number of hotspots and the annual reduction in forest area, indicating that in 80% of the cases, the greater the reduction in forest area , the greater the number of hotspots recorded, making it possible to relate deforestation to anthropic actions. The hotspots occurred mainly in the month of September, coinciding with the prohibitive period of fires and with the lowest flows recorded during the dry season. The analysis of water supply and demand of water courses was carried out using the reference flow, which corresponds to the flow available in 95% of the time (Q95), in addition to surface water abstraction data for irrigation, aquaculture and animal watering. In our study, we identified forty points of surface water collection, with flow and satisfactory access for the supply of water trucks. This approach can be applied at other spatial scales, offering tools for local authorities in planning, decision-making and resource allocation in fighting forest fires and managing water resources.